Estudos de determinante e sistema linear: uma metodologia de ensino contextualizado - LIMA, Denise Silva de (2022)
This course conclusion work has as its approach the determinant studies and linear system with emphasis on a contextualized teaching methodology. In the case of contextualization, we seek to develop, from a theoretical point of view, the mathematical formalism with the (properties) developed analytically. To apply the theoretical study, it is considered a methodology in which it is possible to show applicability in (situations) problems that evidence the practice in which the student will be able to investigate and understand how to equate and solve questions of determinants and linear systems. In this case, the research is directed towards a methodology in which theory and practice are present so that it is possible to verify that learning is only completed when the student is able to understand the themes in the school environment and is able to associate in situations of your everyday life. The research concludes considering that the methodology developed based on contextualization can facilitate as long as it is applied in the context of the classroom and associated with everyday life so that teaching and learning are very promising, given that it brings the student closer to a dynamic, curious and motivating way due to the association between theory and practice.